The determination of the effects of physical and chemical parameters on the column flotation cell, performance in the flotation of pyrite - Schommarz, Klaus Helmuth (Department of Chemical Engineering, 2016)
This masters dissertation an column flotation is to determine the effects of physical and chemical parameters on the column flotation cell performance in the flotation of pyrite. Hypotheses are also proposed to explain observed changes. Chapter one gives a brief description of flotation columns, some applications of flotation columns and a literature survey that covers the effects of various physical and chemical parameters. Chapter two states the objective of this research and the plan of action used to achieve this objective. Chapter three describes the first part of the plan of action, namely to design a laboratory flotation column and to draw up an experimental procedure. A flotation column rig with an adequately repeatable experimental procedure is the result. The repeatability and sensitivity of the experimental procedure is given in chapter four. This chapter also includes the results obtained when the physical and chemical parameters are varied. The effects on the flotation cell performance by varying parameters are summarised. The biggest changes observed in the flotation column cell performance are as follows: 1) An increased air rate yields an optimum sulphur recovery. 2) Concentrate sulphur grades decrease when the air rate is increased. 3) The concentrate grades increase when the froth depth is increased. 4) Increasing the feed solids percent to the flotation column has no effect on the concentrate grades and recoveries as long as the column is operated below its maximum carrying capacity. 5) The concentrate grades are improved by adding wash water. Chapter five then discusses the changes observed in the flotation column cell performance. Chapter six covers the design of a pilot plant flotation column rig, the results obtained on plant and the discussion of these results. It is found that the pilot plant rig can be effectively used for on site test work. The flotation column cell performed better than the conventional cells. The pilot plant test work showed that: 1) Increasing the air rate increases the recovery. 2) Increasing the wash water rate improves the concentrate grades. Finally, in chapter seven, conclusions are drawn regarding the results and discussions. Some of these conclusions are: 1) The flotation column cell performes better than conventional flotation cells due to the column's deep water washed froth and counter-current contact mechanism. 2) Increasing the air rate decreases the grades of the concentrate due to increased entrainment, while the recovery moves through an optimum. 3) Increasing the froth depth increases the concentrate grades due to a longer cleaning action. For the same reason the recovery decreases. 4) The feed solids percentage has no effect on the grade or recovery. Should the maximum carrying capacity however be reached the recovery will drop. 5) Froth stability is essential for good concentrate grades and recoveries. 6) Increased wash water rates increase the concentrate grades due to a stronger washing action and more stable froths. 7) The chemical parameters which are varied show the same trends as was observed in conventional flotation. All data obtained during the test work is attached in the appendices.